CHEMICAL WEAPON USAGE RELATED TO SELF-DEFENSE ARRANGEMENT IN ARTICLE 51 OF THE UNITED NATIONS CHARTER - Rizka Faradilla; Adwani Adwani (Student Journal of International Law, 2022)
Abstract- This paper aims to find out the regulation and the use of chemical weapons as a state’s self-defense and to explain why some countries use chemical weapons to defend themselves from attacks by other countries. This study was conducted based on normative legal method. It was found that Article 51 of the United Nations Charter, which regulates self-defense, does not specifically explain the use of permissible weapons in self-defense, so in practice, there are still many countries that use chemical weapons despite their use being forbidden in war (humanitarian law). The United Nations should amend to the contents of the United Nations Charter, especially in Article 51 on Self-defense, in order to add more detailed rules regarding anticipatory actions for self-defense so that no country admits to carrying out armed attacks with the aim of self-defense for their respective interests and harming many parties.